Interaction of nomination types in the sphere of perfume and cosmetic naming - Нікіфорова , Євгенія; Biletska , Tetiana; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2021)
This article deals with the aspect of naming the perfume and make-up goods. Special attention is given to the specifications of goods names in the sphere of interacting with the nomination types. Perfume and cosmetic names are created involving primary and secondary types of nomination and simultaneously describing corresponding features, qualities and individual characteristics of these goods. In the case of a primary nomination, a motivation feature is designated with a word that has the basic meaning containing the indication of the motivation feature. Name meaning correlates with the reality which is denotated and causes the direct reflection of object features. In the case of a secondary nomination, the indication of the distinguished feature is realized through comparison or confrontation with another object having the same features. Perfume and cosmetic naming is realised within the frame of the naming complex. This complex contains two naming components: the individual name and the goods name. Functioning within one common naming complex, these two names influence each other. Perfume goods creating aromatic, fragrant effect have olfactory feature as their basic characteristics. It means that combinations of smell, scent, aroma, fragrance concentrated in aromatic solutions of different substances correspond to the essential requirements to aromatic liquid goods. The goods in the branch of make-up creating visual effect have colour and colouring as their basic characteristics. The process of secondary naming, when perfume and make-up goods obtain individual names, consists of four basic stages: (1) archseme fading; (2) seme displacement; (3) potential seme actualisation; (4) occasional seme formation. At the very end of these transformations, the individual name is turned into a semantic derivative, the product of a secondary nomination. The most frequent semantic derivation for creating perfume and make-up names is metaphorical transferring that is based on the feature resemblance of two objects which are not connected with reality. The semantic structure of individual names of naming frames is the reflection of the relation existing between objects of extralinguistic reality. It also reflects the results of the cognitive activity of a nominator. The process of the name functional adaptation takes place when the individual names create passing from the primary to the secondary nomination.